Evaluation of the Spelling Component in First-Grade and Second-Grade Syrian Curriculum of English, Emar (Journal of Hama University, 2025)
When developing new curricula for language learners, attention should be given to all components of language. This can be of special importance when dealing with foreign young learners as they are newly introduced into the language. Syrian learners in the first and second grades can find the spelling system in English challenging since spelling is one of the important skills to master when writing in English is taken into consideration. The present study is an attempt to evaluate the spelling component in the newly-designed first-grade and second-grade Syrian Curriculum of English, Emar. The aim of the study is to shed light on the positive points of the way spelling is introduced to young learners. It also looks into the drawbacks that teaching orthography in English based on the curriculum can have. The study demonstrates how the curriculum adopts the traditional approach to teaching spelling. Suggestions related to improving the spelling component in the curriculum are presented, and thus recommendations are made to introduce some modifications in the curriculum.
Keywords: Emar; English curriculum; orthography; spelling